Role of Bangladesh Small and Cottage Industries Corporation in Poverty Reduction. (March 2015) - Haider, Mohammed Ziaul; Dutta, Champa Bati; Siddiqui, Ohidul Islam
This study investigates the role of Bangladesh Small and Cottage Industries Corporation (BSCIC) in poverty reduction of Bangladesh. A total of 91 workers are surveyed who work in BSCIC estates and non-BSCIC manufacturing firms in the south-west region of Bangladesh. This study has used both panel and cross-section approaches. The study findings indicate that BSCIC has a significant role in industrial expansion and poverty reduction in Bangladesh. The regression results reveal that BSCIC significantly influences household consumption and poverty reduction. A 1 per cent increase in income from BSCIC will increase the yearly household consumption by 0.73 per cent, whereas it is only 0.36 per cent in case of non-BSCIC income. The impact of income increase on consumption is more than double for the BSCIC group households in comparison with non-BSCIC group households. In cross-section analysis, the purchasing power parity (PPP) at local currency of US$ 1.25 is considered in this study to construct poverty line. The result shows that, for an increase in the income from BSCIC by US$ 1 per month, income over poverty line increases (or the poverty gap decreases) by US$ 0.028 per month per household on average. Therefore, this study suggests for planned expansion of BSCIC for poverty reduction in Bangladesh.